2013
DOI: 10.1002/macp.201300388
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral Oligosilsesquioxane (POSS) Nanoparticle Localization in Ordered Structures Formed by Solvated Block Copolymers

Abstract: The coassembly of polyhedral oligosilsesquioxanes (POSS) of two different surface chemistries is considered, one hydrophilic, poly(ethylene oxide) (PEO), and the other hydrophobic, isobutyl (iB), in cylindrical structures formed by hydrated poly(ethylene oxide)‐poly(propylene oxide)‐poly(ethylene oxide) block copolymer, Pluronic P105 (EO37PO56EO37). Incorporation of PEO‐POSS by replacing an equal mass of water results in an increase in the lattice parameter (d), which is attributed to an increase in the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Structure formation and nanoparticle localization in nanoparticle-LLC composites in molecular solvents, 192,208,209 and LLC structures formed in ionic liquids have been studied. However, ionic liquid-based nanoparticle-LLC composites are much less studied compared with those in regular solvents.…”
Section: Discussionmentioning
confidence: 99%
“…Structure formation and nanoparticle localization in nanoparticle-LLC composites in molecular solvents, 192,208,209 and LLC structures formed in ionic liquids have been studied. However, ionic liquid-based nanoparticle-LLC composites are much less studied compared with those in regular solvents.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in lattice parameter can be attributed to the swelling of the polymeric domain by NPs [75,154]. For example, the incorporation of deprotonated silica nanoparticles in cylindrical A c c e p t e d M a n u s c r i p t 20 structure formed by hydrated PEO-PPO-PEO BCP increased the lattice parameter at a fixed BCP/water ratio (see Fig.…”
Section: Effect Of Nanoparticles On Characteristic Length-scalesmentioning
confidence: 93%
“…10 The tailored physicochemical properties of the POSS molecules allow them to be used in grafting, blending, and copolymerizing to alter the mechanical strength, thermal stability, glass transition temperature, or crystallization process. 11,12 An exhaustive study of self-assembly of hybrid-polymers utilizing POSS core framework can be found in the review article by Zhang et al 13 Artificially prepared biocompatible advanced materials employ the POSS framework due to their nanosize and robust chemical framework to synthesize bioengineered tissue materials, biocomposites, luminophores, and optical sensors. 14,15 POSS nanocages have been utilized to fabricate photosensitive molecular switches, which demonstrated a unique reversible transformation between cubic lattice and helical superstructures.…”
Section: ■ Introductionmentioning
confidence: 99%